2015
DOI: 10.1007/7854_2015_404
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Influences of Valproate on Brain and Behaviour: An Animal Model for Autism

Abstract: Valproic acid or valproate (VPA) is an anti-convulsant and mood stabiliser effective in treating epilepsy and bipolar disorders. Although in adults VPA is well tolerated and safe, there is convincing evidence that it has teratogenic properties, ranging from mild neurodevelopmental changes to severe congenital malformations. In particular, studies involving humans and other animals have shown that prenatal exposure to VPA can induce developmental abnormalities reminiscent of autism spectrum disorder (ASD). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 126 publications
2
36
0
Order By: Relevance
“…Our data support this hypothesis in an animal model, showing a suppression of predisposed preferences to dynamic as well as static cues to social stimuli in domestic chicks exposed to VPA, a drug used to induce ASD-like behavioral deficits in vertebrate species (Ranger and Ellenbroek, 2016). The observation of a similar impairment in predispositions in different species for both static and dynamic cues suggests a common developmental origin of these social-orienting predispositions.…”
Section: Discussionsupporting
confidence: 84%
“…Our data support this hypothesis in an animal model, showing a suppression of predisposed preferences to dynamic as well as static cues to social stimuli in domestic chicks exposed to VPA, a drug used to induce ASD-like behavioral deficits in vertebrate species (Ranger and Ellenbroek, 2016). The observation of a similar impairment in predispositions in different species for both static and dynamic cues suggests a common developmental origin of these social-orienting predispositions.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, in one of the most recent, large-scale, population-based studies conducted in Denmark, 4.4% of individuals prenatally exposed to VPA developed ASD, compared to 1.5% of controls not exposed to VPA - indicating a near 3-fold increased risk for ASD in those prenatally exposed to VPA (Christensen et al, 2013 ). In line with these findings, studies in rats and mice have shown that prenatal exposure of VPA [usually a single injection on gestational day (GD) 12] induces increases in repetitive behaviors and disruptions of social behavior (Schneider and Przewlocki, 2005 ; Ranger and Ellenbroek, 2015 ).…”
Section: Introductionmentioning
confidence: 85%
“…Although VPA is well tolerated and safe in adults, there is evidence of its teratogenicity [14]. Clinical studies over the years have shown that intrauterine exposure to VPA is associated with birth defects, cognitive impairments, and an increased risk of autism [13].…”
Section: Vpa and The Vpa Animal Modelmentioning
confidence: 99%
“…The compound VPA is a drug widely used as an anticonvulsant and mood stabilizer in the treatment of epilepsy and bipolar disorder [13,14]. Although VPA is well tolerated and safe in adults, there is evidence of its teratogenicity [14].…”
Section: Vpa and The Vpa Animal Modelmentioning
confidence: 99%